Persepsi Masyarakat Desa Jambu, Kecamatan Kledung, Kabupaten Temanggung Terhadap Gangguan Monyet Ekor Panjang - Wahyuni Fitria; A.N. Bambang; J.W. Hidayat (xxxx-xxxx, 2020)
Fitria W, Bambang AN, Hidayat JW.  2020.  Local People’s Perception of jambu village, kledung district, temanggung regency to the long-tailed macaque disturbance. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang  20 Oktober 2020. pp. xx.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).In recent years, the disturbance of long-tailed macaques (Macaca fascicularis) in cultivated plants has become a threat to communities near forest because it caused in significant economic losses. The interaction between humans and wildlife often creates different perceptions that determine the success of treatment efforts. The purpose of this study is to determine the general description of long-tailed macaque disturbance and public perception in responding to it so that effective treatment strategies can be formulated. The research method used is descriptive quantitative and qualitative where data collection is done through a survey with a questionnaire and interviews with respondents. The research result shows that almost all the people of Jambu Village have suffered losses due to long-tailed macaque disturbance that has occurred in the last 5-10 years with more than 20 individuals. Macaque that often attack fields consist of all age groups from puppies to adult individuals. Most people do not know the status and benefits of long-tailed macaque ecologically, biomedically, and economically, but they understand the causes of macaque's infesting fields and settlements, namely the need for food sources. Despite being a threat to the economy and safety, most people can accept the existence of long-tailed macaques if they live in the forest. From the research results, it can be concluded that the majority of the Jambu Village community has a negative perception of long-tailed macaques but has tolerance for their presence in the forest so that conservation-based management strategies can be implemented with community participation.